Discovery of Aspergillus mycoviruses and development of mycovirus-based vector for gene silencing in the human pathogenic fungus Aspergillus fumigatus - Atcharawiriyakul, Jirawalun; Coutts, Robert; Wingfield, Lakkhana K. (Asia-Pacific Journal of Science and Technology, 2021)
A collection of Aspergillus environmental isolates was screened for the presence of mycoviruses. Out of 178 isolates, 5.1% contained double-stranded RNA (dsRNA) elements ranging in size from approximately 0.7 to 6.0 kbp. The dsRNA elements were identified as belonging to four different categories comprising non-segmented dsRNA, bipartite dsRNA, quadripartite dsRNA and uncharacterized mycoviruses. Aspergillus fumigatus tetramycovirus-1 (AfuTmV-1) was exploited for development as a tool for silencing genes in the human pathogenic fungus A. fumigatus. Using a sequence of dsRNA2 belonging to the AfuTmV-1, a recombinant virus vector was engineered to generate the silencing vector AfuTmV-1-dsRNA2::ALB1 which carried a target ALB1/PKSP gene responsible for spore pigmentation. The engineered virus vector induced loss of conidial pigmentation in the fungal host at different levels and with low frequency. In addition, in vitro translation of mycovirus-based silencing vectors demonstrated that the engineered mycoviral vector was functionally transcribed and translated.